Global patterns of antibiotic resistance in group B Streptococcus: a systematic review and meta-analysis - Hsu, Chou-Yi; Moradkasani, Safoura; Suliman, Muath; Uthirapathy, Subasini; Zwamel, Ahmed Hussein; Hjazi, Ahmed; Vashishth, Raghav; Beig, Masoumeh (Frontiers in Microbiology, 2025)
ObjectivesStreptococcus agalactiae, or group B Streptococcus (GBS), is a significant pathogen associated with severe infections in neonates, particularly sepsis and meningitis. The increasing prevalence of antibiotic resistance among GBS strains is a growing public health concern, necessitating a comprehensive meta-analysis to evaluate the prevalence of this resistance globally.MethodsWe conducted a comprehensive systematic search across four major scientific databases: Scopus, PubMed, Web of Science, and EMBASE, targeting articles published until December 13, 2023. This meta-analysis focused on studies that examined antibiotic resistance in GBS strains. The Joanna Briggs Institute tool was employed to assess the quality of the included studies. This meta-analysis applied a random-effects model to synthesize data on antibiotic resistance in GBS, incorporating subgroup analyses and regression techniques to explore heterogeneity and trends in resistance rates over time. Outliers and influential studies were identified using statistical methods such as Cook’s distance, and funnel plot asymmetry was assessed to evaluate potential publication bias. All analyses were conducted using R software (version 4.2.1) and the metafor package (version 3.8.1).ResultsThis study included 266 studies from 57 countries, revealing significant variability in GBS antibiotic resistance rates. The highest resistance rates were observed for tetracycline (80.1, 95% CI: 77.1–82.8%), while tedizolid (0.1, 95% CI: 0.0–0.8%) showed the lowest resistance rates. Significant heterogeneity in resistance rates was observed, particularly for antibiotics such as azithromycin and gentamicin (I2 = 97.29%), variability across studies. On the other hand, tigecycline and ceftaroline exhibited no heterogeneity (I2 = 0%), suggesting consistent resistance patterns. Subgroup analyses revealed disparities in resistance rates based on country, continent, and methodological categories. Significant increase in resistance rates for several antibiotics over time, including clindamycin, erythromycin, ceftriaxone, cefuroxime, ciprofloxacin, levofloxacin, moxifloxacin, chloramphenicol, and ofloxacin. Ofloxacin and cefuroxime showed particularly steep trends. Conversely, a declining resistance trend was observed for oxacillin.ConclusionThis study emphasizes the growing issue of antibiotic resistance in GBS strains. Notable resistance to older and newer antibiotics, increasing resistance over time, regional disparities, and methodological variations are noted. Rising resistance trends for multiple antibiotics underscore the urgent need for global surveillance and improved antibiotic stewardship.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024566269, CRD42024566269.